2019
DOI: 10.3390/life9030061
|View full text |Cite
|
Sign up to set email alerts
|

Cultivar-Specific Performance and Qualitative Descriptors for Butterhead Salanova Lettuce Produced in Closed Soilless Cultivation as a Candidate Salad Crop for Human Life Support in Space

Abstract: Plant production is crucial for space journeys self-autonomy by contributing to the dietary intake necessary to sustain the physical and psychological well-being of space colonists, as well as for contributing to atmospheric revitalization, water purification and waste product recycling. Choosing the appropriate cultivar is equally important as the species selection, since cultivar influences the obtained fresh biomass, water use efficiency (WUE), growing cycle duration, qualitative features and postharvest pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 43 publications
(71 reference statements)
8
26
0
1
Order By: Relevance
“…The non-destructive measurements of chlorophyll content (SPAD Index) [30] measured by El-nakhel et al [31], reflected the changes obtained regarding chlorophyll pigment measurements in our work. Indeed, chlorophyll increased significantly with lettuce maturation, and in both harvest stages was significantly higher in red Salanova, which was the exact same trend observed with chlorophyll measurements of lettuce at 4 and 19 DAT [31]. In photosynthetic tissues, carotenoids, and chlorophylls a and b operate in light harvesting and perform tasks in photo-protection by quenching free radicals, singlet oxygen, and other reactive species [30].…”
Section: Pigments and Total Ascorbic Acid Content Of Microgreens And supporting
confidence: 82%
See 2 more Smart Citations
“…The non-destructive measurements of chlorophyll content (SPAD Index) [30] measured by El-nakhel et al [31], reflected the changes obtained regarding chlorophyll pigment measurements in our work. Indeed, chlorophyll increased significantly with lettuce maturation, and in both harvest stages was significantly higher in red Salanova, which was the exact same trend observed with chlorophyll measurements of lettuce at 4 and 19 DAT [31]. In photosynthetic tissues, carotenoids, and chlorophylls a and b operate in light harvesting and perform tasks in photo-protection by quenching free radicals, singlet oxygen, and other reactive species [30].…”
Section: Pigments and Total Ascorbic Acid Content Of Microgreens And supporting
confidence: 82%
“…In the current study, the loading matrix indicates that variation in lutein and β-carotene was most closely aligned with total chlorophyll, whereas variation in nitrate was not correlated with total polyphenol content ( Figure 2). The effectiveness of PCA in interpreting species/cultivars differences across several functional quality attributes in response to a wide range of preharvest factors such as the genetic material, the maturity stage, environmental conditions and agricultural practices have been reported previously by several researchers [5,6,9,31]. This was also the case of this study conducted under fully controlled conditions, since the score plot of PCA integrated information about the nutritional and functional profile of the red and green-pigmented lettuce harvested at microgreens or at mature stage (Figures 2 and 3).…”
Section: Polyphenols Profile Of Microgreens and Mature Salanovamentioning
confidence: 79%
See 1 more Smart Citation
“…In addition, leaf pigmentation significantly correlates to the constitution and concentration of phenolic compounds belonging mainly in the subgroups of phenolic acids, flavonoids, and anthocyanins [14]. Chicoric, caffeic, and chlorogenic acids and their derivatives are the most abundant phenolic acids present in lettuce, whereas the most outstanding flavonoids include anthocyanins, quercetin, kaempferol, and flavone luteolin [35,[45][46][47]. Several authors reported a higher total phenolic content in red butterhead, red leaf and red romaine lettuces compared to their green counterparts [16,35,[48][49][50][51].…”
Section: Lettucementioning
confidence: 99%
“…A range of crops have been suggested for space life support systems, including leafy greens and vegetables as supplemental foods for early missions (Tibbitts and Alford, 1982;Massa et al, 2015;El-Nakhel et al, 2019), as well as staple type grains, legumes, and tuberous crops for more full nutrition on future missions (Tibbitts and Alford, 1982;Waters et al, 2002;Wheeler, 2017). A species found on many of these crop lists is potato, Solanum tuberosum L. (Tibbitts and Alford, 1982;.…”
Section: Introductionmentioning
confidence: 99%